En ny tysk-islandsk ordbog. Metode og problemer - Kvaran, Guðrún; Steinarsson, Heimir Steinarsson (Nordiske Studier i Leksikografi, 2007)
A new German-Icelandic dictionary. Methods and problems. The paper describes a dictionary work in progress. PONS Dictionary Edition in Stuttgart provided the dictionary’s source, besides the program and the technological knowledge. The source comprises approximately 40,000 headwords (main and sub-headwords including compounds) and 25,000 phrases (grammar constructions, collocations, idioms, proverbs and example sentences), covering the central lexicon of German. Acronyms, abbreviations, and short forms are listed. Specialized vocabulary from the fi elds of business, law and computing has been incorporated – and as a refl ection of increasing specialization in everyday life, the macrostructure also includes specialized vocabulary that is vital in contemporary day-to-day communication at home, school, and in the business world. The emphasis is on modern, up-to-date language, and special attention has been paid to culture-specifi c vocabulary (foods, institutions, customs, etc.), as well as neologisms.